Birth, meaningful viability and abortion. Issue 6 (10th July 2014) - Jensen, David
Abstract : What role does birth play in the debate about elective abortion? Does the wrongness of infanticide imply the wrongness of late-term abortion? In this paper, I argue that the same or similar factors that make birth morally significant with regard to abortion make meaningful viability morally significant due to the relatively arbitrary time of birth. I do this by considering the positions of Mary Anne Warren and José Luis Bermúdez who argue that birth is significant enough that the wrongness of infanticide does not imply the wrongness of late-term abortion. On the basis of the relatively arbitrary timing of birth, I argue that meaningful viability is the point at which elective abortion is prima facie morally wrong.